Internet connectivity disruption in Tanzania (Tanzania) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Tanzania. Data sourced from IODA.
Network Disruption Incident ID: TZ-2026-0028. Severity: critical. Confidence: 70%